Chemical Synthesis of Monolignols: Traditional Methods, Recent Advances, and Future Challenges in Sustainable Processes - Davide Benedetto Tiz; Giorgio Tofani; Filipa A. Vicente; Blaž Likozar (MDPI AG, 2024)
Monolignols represent pivotal alcohol-based constituents in lignin synthesis, playing indispensable roles in plant growth and development with profound implications for industries reliant on wood and paper. Monolignols and their derivates have multiple applications in several industries. Monolignols exhibit antioxidant activity due to their ability to donate hydrogen atoms or electrons to neutralize free radicals, thus preventing oxidative stress and damage to cells. Characterized by their alcohol functionalities, monolignols present three main forms: p-coumaryl alcohol, coniferyl alcohol, and sinapyl alcohol. In nature, particularly in plants, monolignols with geometry (E) predominate over their Z counterparts. The methods for obtaining the three canonical monolignols, two less-common monolignols, and a monolignol analogue are addressed to present an overview of these phenol-based compounds, particularly from a synthetic standpoint. A SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis is used to explain the advantages and disadvantages of synthesizing monolignols, key alcohol-containing raw materials with enormous significance in both plant biology and industrial applications, using bench chemical methods. The uniqueness of this work is that it provides an overview of the synthetic pathways of monolignols to assist researchers in pharmaceutical and biological fields in selecting an appropriate procedure for the preparation of their lignin models. Moreover, we aim to inspire scientists, particularly chemists, to develop more sustainable synthetic protocols for monolignols.